2020
DOI: 10.3390/jfmk5040096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Energy Availability in Collegiate Women Soccer Athletes

Abstract: (1) Background: Limited information exists on the prevalence of low energy availability (LEA) in collegiate team sports. The purpose of this study was to examine the prevalence of LEA in collegiate women soccer players. (2) Methods: Collegiate women soccer athletes (n = 18, height: 1.67 ± 0.05 m; body mass: 65.3 ± 7.9 kg; body fat %: 24.9 ± 5.6%) had their body composition and sport nutrition knowledge assessed in the pre-season. Energy availability was assessed mid-season using a 4-day dietary log and activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
5
26
1
Order By: Relevance
“…Prevalence of LEA among certain National Collegiate Athletic Association (NCAA) Division I athletes has ranged from 41% in cross country runners [ 16 ] to 51% in track and field athletes [ 17 ]. Further, athletes competing in team field sports with a high aerobic component (i.e., soccer), tend to also be at a higher risk, likely due to the high activity energy expenditures [ 3 , 18 ] associated with the sport, with prevalence of LEA ranging from 11% [ 19 ] to 67% [ 18 ], depending upon the time point throughout the season (i.e., off-season vs. pre-season vs. in-season).…”
Section: Prevalence Of Low Energy Availabilitymentioning
confidence: 99%
“…Prevalence of LEA among certain National Collegiate Athletic Association (NCAA) Division I athletes has ranged from 41% in cross country runners [ 16 ] to 51% in track and field athletes [ 17 ]. Further, athletes competing in team field sports with a high aerobic component (i.e., soccer), tend to also be at a higher risk, likely due to the high activity energy expenditures [ 3 , 18 ] associated with the sport, with prevalence of LEA ranging from 11% [ 19 ] to 67% [ 18 ], depending upon the time point throughout the season (i.e., off-season vs. pre-season vs. in-season).…”
Section: Prevalence Of Low Energy Availabilitymentioning
confidence: 99%
“…The Triad occurs in female high school, collegiate, and elite athletes [6,7]. In collegiate athletes, Triad components have the following prevalence estimates: Low EA (11.8-67%) [8,9], MI (16-36%) [8,[10][11][12][13], and low BMD (Z-score < −1) (1-3.5%) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that collegiate women athletes specifically may have a misunderstanding of the advanced dietary requirements of their sport, which also appears to be accompanied by discrepancies between perceived dietary intakes and calculated dietary intakes [ 8 , 11 , 19 ]. Such a lack of sport nutrition knowledge in women athletes may be compounded with body image issues or a drive for thinness, likely underpinned by societal expectations or aesthetically influenced beliefs and ultimately conflating the issue of adequate fueling for their sport [ 8 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%